An Endoscopic Approach to External Auditory Canal Osteoma Excision: A Rare Case Report - Apurva Anil Jarandikar; Diksha B Sangale; Rashmi Prashant Rajashekhar (Journal of Clinical and Diagnostic Research)
External Auditory Canal (EAC) osteoma is an infrequent, unilateral, benign, solitary neoplasm with relatively slow growth. It appears as a single, pedunculated hyperdense lesion. These lesions remain asymptomatic and are often found incidentally, being treated conservatively. However, in larger lesions that obstruct the EAC, they may infrequently exhibit otalgia, conductive hearing loss, tinnitus, a sense of mass, or aural fullness. Histopathological findings, radiographic imaging, and clinical examination may all be utilised to provide a diagnosis. Although asymptomatic cases are managed conservatively, symptomatic and large EAC osteomas are treated with surgical excision, which can be approached endoscopically or microscopically via endaural, transcanal, or postaural approaches. This case involves a 28-year-old male patient who visited the ENT department complaining of a mass in his right EAC, decreased hearing, and a sensation of blockage in the right ear that had been present for 1.5 years. Imaging and histopathological analysis determined it to be a right EAC osteoma. An endoscopic approach was employed for the surgical excision of the bony mass. This approach has been found to facilitate faster postoperative recovery, with better analgesia and cosmesis.